(untitled) (London Journal of Medical and Health Research, 2026)
Cellulite is a common aesthetic concern that may significantly impact on individuals’ self-image and quality of life. Despite being a non-threatening condition, it may have a negative effect on the psychological well-being of affected individuals. This condition is multifactorial and involves several physiopathology pathways. The role of enzymes in the management of cellulite is a novel approach, particularly lipase and collagenase, which play key roles in adipocyte size reduction and collagen degradation, respectively. The potential of high-molecular-weight hyaluronic acid to promote tissue repair and regeneration is also highlighted. Our case report describes the effectiveness of an association of recombinant enzymes and high-molecular-weight hyaluronic acid by reducing cellulite manifestations in a patient, with a history of multiple unsuccessful treatments, showing visible improvements from the initial treatment session. The importance of understanding the complex physiopathology of cellulite and choosing a targeted approach is emphasized.